Sequence polymorphism of the predicted human metapneumovirus G glycoprotein - Peret, Teresa C. T.; Abed, Yacine; Anderson, Larry J.; Erdman, Dean D.; Boivin, Guy (Journal of General Virology, 2004)
The putative G glycoprotein genes of 25 human metapneumovirus (hMPV) field isolates obtained during five consecutive epidemic seasons (1997 to 2002) were sequenced. Sequence alignments identified two major genetic groups, designated groups 1 and 2, and two minor genetic clusters within each major group, designated subgroups A and B. Extensive nucleotide and deduced amino acid sequence variability was observed, consisting of high rates of nucleotide substitutions, use of alternative transcription-termination codons and insertions that retained the reading frame. Deduced amino acid sequences showed the greatest variability, with most differences located in the extracellular domain of the protein: nucleotide and amino acid sequence identities for the entire open reading frame ranged from 52 to 58 % and 31 to 35 %, respectively, between the two major groups. Like the closely related avian pneumovirus and human and bovine respiratory syncytial viruses, the predicted G protein of hMPV shared the basic features of a type II mucin-like glycosylated protein. However, differences from these related viruses were also observed, e.g. lack of conserved cysteine clusters as seen in human respiratory syncytial virus and avian pneumovirus. The displacement of genetic groups of hMPV observed during the study period suggests that potential antigenic differences in the G glycoprotein, which have evolved in response to immune-mediated pressure, may influence the circulation patterns of hMPV strains.